Economic Valuation of the Urban Parks in Kathmandu Valley, Nepal - Khadka, Dipika; Neupane, Dinesh; Sapkota, Ramesh Prasad (Nepal Journal of Environmental Science, 2025)
Urban parks are essential for connecting people with nature and providing social, psychological, and ecological benefits, along with vital ecosystem services. This study focuses on the economic valuation of four urban parks in Kathmandu Valley: Shankha Park, Ratna Park, Balaju Park, and Tribhuvan Park. One hundred and sixty respondents, with 40 respondents from each park were surveyed to assess visitation pattern, satisfaction levels, and willingness to pay (WTP) for park maintenance. Approximately 66% of respondents expressed a willingness to pay for maintenance, indicating the recognized value of these parks, regardless of income levels. The Travel Cost Method (TCM) analysis revealed that Ratna Park had the highest average travel cost (Rs. 81.25) and the largest annual visitor count (360,030), while Tribhuvan Park recorded the lowest visitor numbers (80,000 annually). These results highlight the pivotal role of accessibility, proximity, and park quality in shaping visitation patterns and preferences. Key Informant Interviews (KIIs) highlighted the cultural and ecological importance of the parks, alongside challenges of poor waste management, inadequate fencing, and limited infrastructure in larger parks. These findings emphasize the need for integrating economic valuation into urban park management to enhance visitor satisfaction, environmental benefits, and long-term sustainability.